A Brief History of the Current Reemergence of Contemplative Education. (July 2015) - Morgan, Patricia Fay
This article explores the history of the current reemergence of a contemplative orientation in education. While referencing an ancient history, it primarily examines the history of contemporary contemplative education through three significant stages, focusing on the third. The first was arguably initiated by the introduction of Buddhism to the United States through Chinese immigration that started in 1840, and the second began in the late 1960s and early 1970s with the establishment of three significant tertiary institutions that engage contemplative practice and theory. The third, which began in 1995 with the founding of the Centre for Contemplative Mind in Society, is introduced through five developmental influences. Linked with this is the concurrent development and growing intersection of contemplative and transformative education. This contemporary and ancient history traces the continuing presence of the contemplative in education to counter suggestions that contemplative education may be a fleeting trend. Rather, it indicates that contemplative practice, which grounds this approach in education, is an essential aspect of who we are and how we learn.